Legal Sanctions Civil State Apparatus Woman as Polygamous Wife - Mustafa Akhwaludin (International Asia Of Law and Money Laundering, 2022)
The legal rules on marriage and divorce for civil servants are regulated in Government Regulation No. 45 of 1990 revised PP No.10 of 1983, the focus of attention in this revision is about the ability of female civil servants to become second, third and fourth wives. Article 4 paragraph 2 PP No. 45 of 1990 expressly does not allow female civil servants (PNS) to become polygamous wives which in the previous rules was allowed with the provision not with male civil servants. This rule is also confirmed by the provision of severe disciplinary sanctions in the morning of female civil servants who violate the dismissed.